Deciphering Solar Magnetic Activity: The Solar Cycle Clock - Leamon, Robert J.; McIntosh, Scott W.; Title, Alan M. (Frontiers in Astronomy and Space Sciences, 2022)
The Sun's variability is controlled by the progression and interaction of the magnetized systems that form the 22-year magnetic activity cycle (the "Hale Cycle"") as they march from their origin at ~55º latitude to the equator, over ~19 years. We will discuss the end point of that progression, dubbed "terminator" events, and our means of diagnosing them. In this paper we expand on the Extended Solar Cycle framework to construct a new solar activity "clock" which maps all solar magnetic activity onto a single normalized epoch based on the terminations of Hale Magnetic Cycles. Defining phase 0 * 2pi on this clock as the Terminators, then solar polar field reversals occur at 0.2 * 2pi, and the geomagnetically quiet intervals centered around solar minimum start at 0.6 * 2pi and end at the terminator, thus lasting 40% of the cycle length. At this onset of quiescence, dubbed a "pre-terminator," the Sun shows a radical reduction in active region complexity and, like the terminator events, is associated with the time when the solar radio flux crosses F10.7 = 90 sfu. We use the terminator-based clock to illustrate a range of phenomena that further emphasize the strong interaction of the global-scale magnetic systems of the Hale Cycle: the vast majority, 96%, of all X-flares happen between the Terminator and pre-Terminator. In addition to the X-rays from violent flares, rapid changes in the number of energetic photons---EUV spectral emission from a hot corona and the F10.7 solar radio flux---impinging on the atmosphere are predictable from the Terminator-normalized unit cycle, which has implications for improving the fidelity of atmospheric modelling.